Analisis Kelayakan Investasi Pengembangan Perumahan Subsidi Di Kabupaten Tangerang - Darryl Arlen Hartanu dan Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Up until now, housing investment is still interesting because the demand for housing remains high. Developers are interested to investing in the house sector because of its promising profits. However, it still needs the investment analysis to minimize the risks. Most developers only calculate investment costs compared to the sales plan. The time value of money is often not calculated eventhough costs in the housing sector investments often require many years. This is a feasibilty study based on a house development project in Tangerang Regency,  which developed by PT. TCM. The developer was willing to provide the necessary data for this study including interview such as house design, siteplan, and financial data. From the project’s financial data , we built the cash flow projection and analyzed the investment using Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI)  methods and to find the project Payback Period (PP). The results of this study indicate that the project is feasible to be developed. The result of the analyze showed NPV scored positive to value of Rp 12.061.187.000,- ; IRR is worth 24,58% > interest rate of 10%, IP worth 1,79 > 1, for payback period is reached after 3 years and 135 days.. Thus the housing developments planning by PT. TCM, in Tangerang Regency is worth to be implemented.